O'Reilly Security Conference 2017, New York, NY. (O'Reilly Media, 2017)
"Security NYC 2017 provided a hype-free, lessons-learned examination of the sophisticated practices and cutting-edge techniques some of the world's best security professionals use to protect their networks, clouds, and data. Defining the speakers who presented at Security NYC 2017 as some of the 'world's best' is not hype; it's the truth. The individuals chosen to speak were peer reviewed by a 40-person program committee consisting of in-the-trenches security practitioners working at companies like American Airlines, Microsoft, MedSec, White Ops, Endgame, Snyk, Fastly, Starbucks, Signal Sciences, VeraCode, and more. This video compilation provides a complete recording of each of the keynote speeches, tutorials, and technical sessions delivered by this esteemed group."--Resource description page